Multicultural in Nursing - differences in caring for a Muslim - Kostka, Anna; Krzemińska, Sylwia Anna; Borodzicz, Adriana Milena (Journal of Education, Health and Sport, 2017)
Every person regardless of age, sex, social status, religion, and the environment have the right to medical care and to equal treatment. Each member of the therapeutic team is to provide the patient with comprehensive care. Lack of knowledge of cultural and religious principles contributes to disturbances in relationships with patients. The followers of Islam function according to rules that differ considerably from the Catholic principles. The task of medical staff is: ensuring safety, adequate conditions for prayer and cleanliness, and care for the exclusion of prohibited products. Knowing the basic principles of Islam will help to understand the patient, his problems and needs, gain his trust, and provide him or her with appropriate care in a time so difficult for each patient.